STUDY ON THE RELATIONSHIP BETWEEN BODY MASS INDEX AND WALKING SPEED IN ADOLESCENTS - Vica Ivașcu; Bogdan Constantin Ungurean (Sport şi Societate)
The study aimed to identify the relationship between body mass index (BMI) and walking speed in adolescents aged 16,5 ± 0,4 years. To evaluate the relationship between these two variables, a Pearson correlation was conducted. A total of 68 students participated in the study: 30 boys and 38 girls. Preliminary analyses showed that the relationship is linear with both variables distributed normally, as evaluated by the Shapiro-Wilk test (p > 0.05), and there were no outlier values. There was a statistically significant positive correlation between BMI and the time obtainedin the shuttle run test, p < 0.001, r = 0,578. At the same time, the use of the Independent Samples Test indicated statistically significant differences in the results obtained by both the groups of boys and girls in the applied tests, with p < 0.001. In conclusion, the results of the study demonstrate that higher values obtained in the shuttle run test are associated with a higher BMI in adolescents.